Comparison of buccal infiltration of 4% articaine with 1 : 100,000 and 1 : 200,000 epinephrine for extraction of maxillary third molars with pericoronitis: A pilot study - Lima Jr., José Lacet (2013)
We compared the buccal infiltration of 4% articaine with 1 : 100,000 or 1 : 200,000 epinephrine without a palatal injection for the extraction of impacted maxillary third molars with chronic pericoronitis. This prospective, double-blind, controlled clinical trial involved 30 patients between the ages of 15 and 46 years who desired extraction of a partially impacted upper third molar with pericoronitis. Group 1 (15 patients) received 4% articaine with 1 : 100,000 epinephrine and group 2 (15 patients) received 4% articaine with 1 : 200,000 epinephrine by buccal infiltration. None of the patients in group 1 reported pain, but 3 patients in group 2 reported pain, which indicated a need for a supplementary palatal injection. The palatal injections were all successful in eliminating the pain. Two additional patients in group 2 experienced pain when the suture needle penetrated their palatal mucosa. Based on these results, 4% articaine with 1 : 100,000 epinephrine was found to be more effective for the removal of upper third molars in the presence of pericoronitis than 4% articaine hydrochloride with 1 : 200,000 epinephrine when only a buccal infiltration was used. © 2013 by the American Dental Society of Anesthesiology.